The Neuroscientific Basis of Successful Design How Emotions and Perceptions Matter - Maiocchi, Marco (PoliMI SpringerBriefs, 2015)
The term "design" today encompasses attributes of artifacts that go beyond their intended functions, imbuing them with new meanings. Those meanings are deeply related to the emotions perceived by the users. This book investigates the findings deriving from the neurosciences that are relevant to design. Drawing upon up-to-date neuroscientific knowledge, the authors define what an emotion is, examine the relationship between perceptions and emotions and discuss the role of metaphoric communication. Particular attention is paid to those elements of perception and metaphoric interpretation that cause the emotions to rise. Consequences for the design process are then considered and a design process is proposed that takes into account emotional impacts as one of the goals. A solid scientific approach to the subject is maintained throughout and understanding is facilitated by the inclusion of a rich collection of successful design artifacts, the emotional aspects of which are analyzed.